PS02.115: PERIOPERATIVE CHEMOTHERAPY VERSUS NEOADJUVANT CHEMORADIATION FOR PATIENTS WITH ADENOCARCINOMA OF THE DISTAL OESOPHAGUS IN AUSTRIA. (14th September 2018) - Koch, Oliver; Tschoner, Andreas; Partl, Richard; Perathoner, Alexander; Gehwolf, Philipp; Weitzendorfer, Michael; Varga, Martin; Kapp, Karin; Függer, Reinhold; Öfner-Velano, Dietmar; Emmanuel, Klaus
Abstract: Background: The aim of this study is to compare the outcome of patients with adenocarcinoma of the distal oesophagus (AEG Type I) treated with perioperative chemotherapy or neoadjuvant chemoradiation. Methods: A retrospective analysis of eligible patients from four Austrian centers was conducted. All patients with AEG type I treated between January 2007 and October 2017 with chemotherapy (EOX-protocol) or chemoradiation (CROSS-protocol, or 5-FU/Cisplatin), followed by oesophagectomy were included in the study. Primary outcomes overall survival, and disease free survival as well as secondary outcomes, achievement of pathological complete response pCR (ypT0N0M0) or downstaging of T- or N-stage were analyzed. Primary outcomes were calculated by the Kaplan-Meier-method. Results: Data of 117 patients were analyzed, 59 received chemoradiation (50/59 CROSS and 9/59 5-FU/Cisplatin) and 58 patients received perioperative chemotherapy (EOX). Complete data at time of submission were available in 40 patients in the chemoradiation group and in 37 patients in the chemotherapy group. The median follow-up time in the chemoradiation group was 13, 0 months (CI 95%: 11, 0–15, 0) and in the chemotherapy group 45, 0 months (CI 95%: 28, 8–61, 3). Overall survival rate in the EOX group after ½, 1, 3 and 5 years was 92%, 83%, 63% and 34%. So far long term data are not available after chemoradiation, after ½ year overall survival was 84% and after one year 60%. Disease free survival rate in the EOX group after ½, 1, 3 and 5 years was 91%, 81%, 54% and 32%, in the chemoradiation group after ½ and one year 80% and 50%. A significant difference was found in the pathological complete response (pCR) rate, it was achieved in 19% of patients after chemoradiation and in 3% after chemotherapy ( P = 0000). Conclusion: Concerning major response of the primary tumor there are clear advantages for chemoradiation. In regards to systemic tumor control there seems a tendency in favor for chemotherapy. Disclosure: All authors have declared no conflicts of interest.